Potensi Penyimpangan Hukum Dalam Peraturan Pemerintah Pengganti Undang-Undang Nomor 1 Tahun 2020 - Ahmad Gelora Mahardika (Fakultas Hukum Universitas Islam Indonesia, 2020)
The development of the Corona Virus Disease-2019 (Covid-2019) was followed-up by the Government by issuing a Government Regulation in lieu of Law Number 1 of 2020 (Perpu Number 1 of 2020). The formulation of the problem to be answered in this research is what is the potential for legal irregularities in Government Regulation in lieu of Law Number 1 Year 2020? The research method used is normative juridical with a statutory approach. The results show that there is a potential for legal irregularities in this Perpu. The deviation in the form of a Perppu contradicts a number of Articles in the Legislation. These violations have the potential to give rise to legal uncertainty, because the Perpu is only temporary, namely until the completion of the Covid-19 pandemic outbreak phenomenon which cannot be ascertained when it will end. On the other hand, this Perpu provides enormous powers for a number of officials to take preventive measures that do not correlate directly with the Covid-19 pandemic problem, one of which is liquidity assistance to banks that are both systemically and non-systemically affected. In addition, all officials are given the right to immunity not to be prosecuted both criminal and civil and the decisions issued are not the object of the PTUN dispute, meaning that there is no checks and balances mechanism in the government. Thus, the suggestion given is to revise this Perpu.